Institutional barriers to medical examinations in Barnahus - Stefansen, Kari (Justice and recovery for victimised children, 2024)
Although ensuring that victimised children receive timely medical health assessments is among the key aims of Barnahus, this goal has proven difficult to achieve in Norway, the empirical case examined in this chapter. Few children are offered a medical examination, and most examinations that are performed primarily serve a role in the “penal track” of the Barnahus model. Based on data from two national evaluation studies, we identify three types of institutional barriers that hamper the role of medical examinations in the “welfare track” of the model: established routines, regulatory issues, and a lack of resources. The concept of institutional inertia is helpful in understanding the institutional resistance towards change that often characterises the present situation.